The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/ilr.12034
|View full text |Cite
|
Sign up to set email alerts
|

Youth employment security and labour market institutions: A dynamic perspective

Abstract: The shift of policy focus from job security to employment security calls for a more dynamic measurement of young people's labour market performance. This article uses data on monthly employment status trajectories and job duration to investigate young Europeans' employment security around five years after they finished education. The authors show that almost 40 per cent of "job-insecure" individuals actually enjoy employment security -i.e. they are able to re-enter paid employment rapidly after losing their jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
7
0
2
Order By: Relevance
“…While previous studies have shown negative effects of EPL on unemployment (see Berloffa et al, 2016), more recent studies have usually found no or only slightly negative effects (Avdagic, 2015;Breen, 2005;Noelke, 2016;Scarpetta, 2014). One assumption is that the influence of EPL is more apparent in the composition of unemployment than in the level of unemployment (Barbieri and Cutuli, 2015).…”
Section: Employment Protection Legislationmentioning
confidence: 97%
See 2 more Smart Citations
“…While previous studies have shown negative effects of EPL on unemployment (see Berloffa et al, 2016), more recent studies have usually found no or only slightly negative effects (Avdagic, 2015;Breen, 2005;Noelke, 2016;Scarpetta, 2014). One assumption is that the influence of EPL is more apparent in the composition of unemployment than in the level of unemployment (Barbieri and Cutuli, 2015).…”
Section: Employment Protection Legislationmentioning
confidence: 97%
“…In most continental countries there has been a strategy since the late 1980s of weakening EPL for workers on the secondary labour market (reducing protection for those with temporary contracts), while maintaining high EPL for core workers. This has created labour market segmentation and may have given rise to new forms of economic and social inequality (Barbieri and Cutuli, 2015;Berloffa et al, 2016;Chung, 2016;Gebel and Giesecke, 2016;Noelke, 2016). There is a general assumption and also evidence that this has led to the substitution of permanent jobs with temporary jobs, as well as reduced mobility from temporary to permanent employment (see Barbieri and Cutuli, 2015;Chung, 2016;Gebel and Giesecke, 2016;Noelke, 2016).…”
Section: Employment Protection Legislationmentioning
confidence: 99%
See 1 more Smart Citation
“…Věkovou segmentací se za pomoci různých přístupů zabývají empirické studie (pro přehled viz Berloffa et al, 2016;srov. rovněž Albert et al, 2008;Tatsiramos, 2010nebo Kelly et al, 2014.…”
Section: Přehled Literatury a Odůvodnění Výzkumných Otázekunclassified
“…Tato na první pohled pozitivní tendence je však spojena s nízkou vymiňovací mzdou mladých nezaměstnaných, přijímáním nestabilních, nevýznamných a hůře placených zaměstnání. Z toho vyplývá, že se ve skutečnosti opět jedná o projev marginalizace mladých lidí na trhu práce (Kelly et al, 2014;Berloffa et al, 2016). 2 Uvedenou specifiku mladých lidí potvrzují i studie, které se zaměřují na stanovení hodnot všech pravděpodobností přechodu mezi stavy na trhu práce v uzavřeném Markovově systému.…”
Section: Přehled Literatury a Odůvodnění Výzkumných Otázekunclassified